2021
DOI: 10.1007/s42108-020-00100-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of Caspian energy markets via a hybrid index for energy demand security in Caspian countries in years 2020 and 2030

Abstract: Establishment of demand security is a key incentive to boosting oil and gas investments in countries, thus, making the study of demand security also critical. In the present research, the primary aim is to explore the capacity of Caspian Markets in establishing energy demand security in the Caspian region and investigate its impact on oil and gas exports from the region. Therefore, additional factors such as political issues, international support and geographical limitations should also be considered for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…The results obtained and presented in Tables 4 and 5 indicate that GDP per capita is indirectly influenced by domestic oil production per capita, trade dynamics, and the share of renewable energy use, with the estimated coefficients being statistically significant at the 5% and 10% significance levels. It was also found that a 10% increase in domestic natural gas production per capita (in the form of lag 1) tends to increase GDP per capita by about 2.90%, which is confirmed by the fact that Uzbekistan is one of the world's largest natural gas producers, producing about 60 billion cubic metres (bcm) annually, of which 35-40 bcm are supplied by Uzbekneftegaz JSC [26,67,68].…”
Section: Results After the Application Of The Mathematical Model At T...mentioning
confidence: 95%
“…The results obtained and presented in Tables 4 and 5 indicate that GDP per capita is indirectly influenced by domestic oil production per capita, trade dynamics, and the share of renewable energy use, with the estimated coefficients being statistically significant at the 5% and 10% significance levels. It was also found that a 10% increase in domestic natural gas production per capita (in the form of lag 1) tends to increase GDP per capita by about 2.90%, which is confirmed by the fact that Uzbekistan is one of the world's largest natural gas producers, producing about 60 billion cubic metres (bcm) annually, of which 35-40 bcm are supplied by Uzbekneftegaz JSC [26,67,68].…”
Section: Results After the Application Of The Mathematical Model At T...mentioning
confidence: 95%